Negative Freedom in the Character of Enola Holmes: Isaiah Berlin’s Perspective on Liberalism - Fatin Kamilia Azzati; Sumayah (Surakarta English and Literature Journal, 2025)
This study explores the portrayal of negative freedom as conceptualized by Isaiah Berlin in the character of Enola Holmes in the film Enola Holmes (2020). The research aims to identify aspects of Berlin’s liberalism reflected in the narrative, to describe how Enola exemplifies the principles of negative freedom, and to highlight the significance of achieving such freedom in a patriarchal society. Employing a qualitative method, this analysis focuses on narrative and visual elements that reflect Berlin’s concept of negative freedom. The data were collected by identifying scenes and applying the theory. Enola’s physical and mental transformation is central to her personal growth, demonstrating how the film explores the themes of self-discovery and autonomy. The findings reveal that Enola’s journey represents a compelling embodiment of Berlin’s negative freedom. At the film's outset, Enola is subjected to patriarchal restrictions, particularly through the control exerted by her brother Mycroft. Her decision to search for her mother marks a pivotal moment in reclaiming her autonomy, as she begins charting her own path. The analysis further demonstrates that Enola’s struggle against societal norms and her eventual selfacceptance signify a transformative journey toward individual freedom. Through her defiance of external controls, Enola exemplifies Berlin’s concept of negative freedom, underscoring the importance of autonomy in fostering personal growth and liberation. This research highlights the enduring relevance of Berlin’s liberal philosophy in contemporary narratives.